The predictors of complications in balloon pulmonary angioplasty for chronic thromboembolic pulmonary hypertension. Issue 6 (17th February 2019) - Ikeda, Nobutaka; Kubota, Shuji; Okazaki, Toru; Iijima, Raisuke; Hara, Hidehiko; Hiroi, Yukio; Nakamura, Masato
Abstract: Objectives: The aims of this study were to (1) evaluate risk factors of complications of balloon pulmonary angioplasty (BPA) and (2) assess the mechanism of the complications. Background: BPA represents a promising treatment option in patients with inoperable chronic thromboembolic pulmonary hypertension (CTEPH). However, the complication ratio differs across reports, and the causes remain controversial. Methods: All complications found by angiography and non‐contrasted computerized tomography (CT) immediately after BPA were recorded. New emergences of a ground‐glass pattern or consolidation in CT after BPA that were not recognized on CT images before BPA were counted as pulmonary bleeding. Lesion morphologies were classified into four types (web, ring, abrupt narrowing and occlusive lesions) according to selective pulmonary angiography. Results: Thirty patients consented to analysis of the BPA‐related images, and 879 lesions (112 sessions) were evaluated. One hundred and twenty‐two (99.2%) of 123 complications were confirmed to be associated with BPA procedures at the local area. In the multivariate analysis, occlusive lesions were the sole independent predictor of procedure‐related complications (adjusted odds ratio 5.83, 95%CI [1.94–17.47], p  = 0.002). Hemodynamic parameters were not predictors of complications. CT images after BPA presented the predictive value for the occurrence of hemoptysis. Conclusions: Almost all complications were attributed to operators' procedures. Lesion morphology was the sole predictor of BPA‐related complications, while hemodynamic parameters were not associated with the frequency of complications. CT scan images after BPA were useful to identify bleeding complications and to predict hemoptysis.